Real estate transaction taxes and credit supply - Koetter, M.; Marek, P.; Mavropoulos, A. (Journal of Financial Stability, 2025)
We exploit staggered real estate transaction tax (RETT) hikes across German states to identify the effect on the growth rates of regional house prices and outstanding mortgage loans by all local German banks. The results show that a RETT hike by one percentage point reduces regional house prices by 3%–4%. Furthermore, IV-regressions yield that a 1 percentage point drop in regional house prices induced by a RETT increase leads to a 0.3% decline in regional mortgage lending, particularly among low-capitalized banks in rural regions.